2022
DOI: 10.1101/2022.02.03.22270306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental health in a diverse sample of healthcare workers during the COVID-19 pandemic: cross-sectional analysis of the UK-REACH study

Abstract: ObjectivesTo investigate how ethnicity and other sociodemographic, work, and physical health factors are related to mental health in UK healthcare and ancillary workers (HCWs), and how structural inequities in these factors may contribute to differences in mental health by ethnicity.DesignCross-sectional analysis of baseline data from the UK-REACH national cohort studySettingHCWs across UK healthcare settings.Participants11,695 HCWs working between December 2020-March 2021.Main outcome measuresAnxiety or depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…These findings align with other research (Martin et al, 2022 ) which identified less access to adequate PPE for ethnic minority HCWs. This situation is associated with decreased trust in employers (as evidenced in this research), which in turn may be associated with a more significant impact on the mental wellbeing of ethnic minority HCWs compared to those from white ethnic backgrounds (Melbourne et al, 2022 ). Inconsistencies in policy guidance may leave HCWs at increased risk of infection from COVID-19, and combined with a lack of trust in employer, may lead to a fundamental sense of betrayal.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These findings align with other research (Martin et al, 2022 ) which identified less access to adequate PPE for ethnic minority HCWs. This situation is associated with decreased trust in employers (as evidenced in this research), which in turn may be associated with a more significant impact on the mental wellbeing of ethnic minority HCWs compared to those from white ethnic backgrounds (Melbourne et al, 2022 ). Inconsistencies in policy guidance may leave HCWs at increased risk of infection from COVID-19, and combined with a lack of trust in employer, may lead to a fundamental sense of betrayal.…”
Section: Discussionmentioning
confidence: 82%
“…In the UK, there is an emerging evidence base that demonstrates similar experiences and outcomes within the general population (Pierce et al, 2020 ) and in particular, HCWs. This emerging research suggests there is a ‘mental health crisis’ for HCWs in the UK (Melbourne et al, 2022 ). Governmental reports have also acknowledged the additional psychological burden on UK HCWs during the pandemic (PHE, 2020a ; House of Commons, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Not applicable. 4 Pennine Care NHS Foundation Trust, Trust Headquarters, 225 Old Street, Ashton-Under-Lyne, Greater Manchester, UK. 5 Greater Manchester Resilience Hub, Pennine Care NHS Foundation Trust, Trust Headquarters, 225 Old Street, Ashton-Under-Lyne, Greater Manchester, UK.…”
Section: Authors' Contributionsmentioning
confidence: 99%
“…The COVID-19 pandemic impacted the mental health of health and social care workers, with staff working in frontline roles and critical care particularly affected, [1,2] especially or those redeployed into new roles [3]. Staff from Black, Asian, and other diverse ethnic communities [4], staff with existing physical or mental health conditions, and those with limited social support were also at high risk of mental health difficulties [2,[5][6][7][8]. Internationally, 49% reported insomnia, 47% anxiety, and 37% post-traumatic stress [9].…”
Section: Introductionmentioning
confidence: 99%
“…Among included studies, three were designed as crosssectional studies [26,27,33], two cohort studies [32,34], two qualitative studies [23,29], and two studies were online surveys [28,31]. One cross-sectional study conducted a qualitative analysis of data from different sources regarding experiences of PPE [30].…”
Section: Study Types and Settingsmentioning
confidence: 99%